1983
DOI: 10.1007/bf00042156
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine-induced variants in sunflower

Abstract: Seedlings of the F, sunflower hybrid between inbred lines AHA 232 (cytoplasmic male sterile, non-branched) and RHA 274 (male fertile, homozygous for dominant fertility restorer and recessive branching) were treated with 0.5 per cent colchicine in lanolin applied to the newly exposed growing point after separation of the cotyledons. Of the 100 treated seedlings 54 survived to produce flowers and 50 set at least some seed. Ten of the treated Fi plants exhibited the recessive characters, branching or male sterili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…According to him, mutagenic action of colchicine was not limited to a single locus of a chromosome but might affect mutations at random involving many genes probably on different chromosomes within that one plant resulting in large number of mutant phenotypes in a single plant as also exhibited in the present dwf1 in grass pea. Colchicine-induced mutants or variants were also recovered earlier in flax (Dirks et al 1956) and soybean (Downes and Marshall 1983).…”
Section: Characteristics Of Three Dwarf Mutantsmentioning
confidence: 90%
“…According to him, mutagenic action of colchicine was not limited to a single locus of a chromosome but might affect mutations at random involving many genes probably on different chromosomes within that one plant resulting in large number of mutant phenotypes in a single plant as also exhibited in the present dwf1 in grass pea. Colchicine-induced mutants or variants were also recovered earlier in flax (Dirks et al 1956) and soybean (Downes and Marshall 1983).…”
Section: Characteristics Of Three Dwarf Mutantsmentioning
confidence: 90%
“…Substantial evidence suggests that colchicine treatment induces deleterious alterations in plant material (Dirk et al, 1956;DOWNES & MARSHALL, 1983;FRANZIE & ROSS, 1952;GILBERT & PATTERSON, 1965) and results from this study were consistent with this evidence. The CDH population differed significantly from the IVDH population for yield and percent alkaloid content (Table 1).…”
Section: Resultssupporting
confidence: 82%
“…The existence of residual heterozygosity as an explanation has been contested for flue-cured tobacco (ARcIA et al, 1978;BROWN & WERNSMAN, 1982), but substantial evidence suggests that heterozygosity is present in inbred lines (EAST, 1935;GRIFFITH et al, 1955;JONES & MANN, 1958;LEGG & COLLINS, 1968;RUSSELL et al, 1963;SPRAGUE et al, 1960). The effect ofcolchicine treatment on doubled-haploid materials has never been fully addressed, although several studies have concluded that colchicine can produce mutations and deleterious changes in treated plant materials (DIRKS et al, 1956;DOWNES & MARSHALL, 1983;FRANZKE & Ross, 1952;GILBERT t~ PATTERSON, 1965). Recent evidence suggests that DNA amplification in the source nuclei of anther-derived haploids may be contributing to the undesirable qualities of these materials (DE PAEPE et al, 1982;DHILLON et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The production of genetic variants by colchicine treatment of apical meristems is similar to the generation of somaclonal mutants by cell culture (Larkin & Scowcroft, 1981 ;Downes & Marshall, 1983) but it is faster and requires no special equipment or expertise . The preliminary investigation reported here suggests that substantial amounts of heritable variation for quantitative characters of economic significance can be produced in cotton, even though no morphological differences were seen .…”
Section: Discussionmentioning
confidence: 78%
“…(1956) used the technique in flax, and Gilbert & Patterson (1965) in barley, although the latter authors were unsuccessful with wheat and oats . Most recently Downes & Marshall (1983) observed aberrant F2 segregation ratios from colchicine-treated hybrids of sunflowers . The colchicine technique is attractive to breeders for three reasons .…”
Section: Introductionmentioning
confidence: 99%